The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1107/s1399004713027466
|View full text |Cite
|
Sign up to set email alerts
|

Stealth carriers for low-resolution structure determination of membrane proteins in solution

Abstract: Structural studies of membrane proteins remain a great experimental challenge. Functional reconstitution into artificial nanoscale bilayer disc carriers that mimic the native bilayer environment allows the handling of membrane proteins in solution. This enables the use of small-angle scattering techniques for fast and reliable structural analysis. The difficulty with this approach is that the carrier discs contribute to the measured scattering intensity in a highly nontrivial fashion, making subsequent data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 84 publications
(110 reference statements)
2
75
0
Order By: Relevance
“…While the E. coli strain AL95/pAC-PCS lp -Sp-Gm was originally engineered to test the effects of the eukaryotic model lipids on bacterial membrane proteins, this project showed that it can also be used as a production platform for physiologically relevant deuterium-labelled phosphatidylcholines and that this approach is also applicable for the deuteration of other physiologically relevant phospholipids and membrane components. The lipids obtained in this way were, in combination with deuterated versions of the ApoA1-derived membrane scaffold proteins (Bayburt et al 2002), recently used in a small-angle neutron scattering study of a so-called stealth nanodisc system contrast optimized for SANS-based structural studies of membrane proteins in solution (Maric et al 2014). Utilizing the novel methods for the production of selectively deuterated, physiologically relevant PCs allowed controlled, site-specific deuteration of three distinct parts of the PC lipid molecule (lipid head group, glycerol backbone, fatty acyl tail) which were successfully used to assemble both neutron-invisible nanodiscs as well as vesicles for use in low resolution structural studies of membrane proteins in solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the E. coli strain AL95/pAC-PCS lp -Sp-Gm was originally engineered to test the effects of the eukaryotic model lipids on bacterial membrane proteins, this project showed that it can also be used as a production platform for physiologically relevant deuterium-labelled phosphatidylcholines and that this approach is also applicable for the deuteration of other physiologically relevant phospholipids and membrane components. The lipids obtained in this way were, in combination with deuterated versions of the ApoA1-derived membrane scaffold proteins (Bayburt et al 2002), recently used in a small-angle neutron scattering study of a so-called stealth nanodisc system contrast optimized for SANS-based structural studies of membrane proteins in solution (Maric et al 2014). Utilizing the novel methods for the production of selectively deuterated, physiologically relevant PCs allowed controlled, site-specific deuteration of three distinct parts of the PC lipid molecule (lipid head group, glycerol backbone, fatty acyl tail) which were successfully used to assemble both neutron-invisible nanodiscs as well as vesicles for use in low resolution structural studies of membrane proteins in solution.…”
Section: Discussionmentioning
confidence: 99%
“…a version of the ApoA1-derived nanodisc carrier (Bayburt et al 2002), which is contrast optimized for SANS-based structural studies of membrane proteins in solution (Maric et al 2014). This approach for SANS contrast optimization is a crucial step as a part of a general quest towards developing nanodisc carriers for low resolution structural studies of membrane proteins in solution or at interfaces (Rambo and Tainer 2013; Skar-Gislinge et al 2010; Wadsater et al 2012; Wadsater et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, a common feature for all previous studies is that they rely on commercially available hydrogenated detergents or fully deuterated detergents developed for different purposes. This is reflected in the resulting neutron scattering data, which include scattering crossterms from the entire detergent-membrane protein complex due to the differences in excess scattering length density of the hydrophobic and hydrophilic parts of the detergents present on length scales of [10][11][12][13][14][15][16][17][18][19][20] A. This effect is difficult to disentangle from the signal from the membrane protein and significantly limits the resolution that can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…BR and KCNE1 reconstituted into SMALPs/Lipodisqs® revealed high-quality DEER-detected distance distributions between selectively incorporated spin labels (Orwick-Rydmark et al, 2012;Sahu et al, 2013), forecasting the applicability of this technique to other MPs in obtaining distance constrains for modeling, and in determining structural dynamics and ligand associations. Further, advances in the implementation and analysis of small-angle X-ray and neutron scattering (SAXS and SANS) experiments show great promise for future work in obtaining low (~10 Å)-resolution structures of nanodisc-incorporated MPs (Kynde et al, 2014;Maric et al, 2014).…”
Section: Structural Studiesmentioning
confidence: 99%